2004
DOI: 10.1016/j.cub.2004.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of Apoptotic Cells Is Regulated by a UNC-73/TRIO-MIG-2/RhoG Signaling Module and Armadillo Repeats of CED-12/ELMO

Abstract: The combination of in vitro and in vivo studies presented here identify two evolutionarily conserved players in engulfment, TRIO/UNC73 and RhoG/MIG-2, and the TRIO --> RhoG signaling module is linked by ELMO/CED-12 to Dock180-dependent Rac activation during engulfment. This work also identifies ARM repeats within CED-12/ELMO and their role in linking RhoG and Rac, two GTPases that function in tandem during engulfment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
155
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(159 citation statements)
references
References 41 publications
3
155
0
1
Order By: Relevance
“…19,20 To address whether CED-2 : CED-5 interaction is required for cell migration, we assayed migration of the gonadal distal tip cells (DTCs), which define the shape of the adult hermaphrodite gonad. 12 Interestingly, expression of CED-5(1-1715) in CED-5-deficient worms was able to rescue DTC migration as efficiently as the wild-type CED-5 (Table 1b). These data suggested that the direct interaction of CED-2 and CED-5 is not required for efficient engulfment or DTC migration in C. elegans.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…19,20 To address whether CED-2 : CED-5 interaction is required for cell migration, we assayed migration of the gonadal distal tip cells (DTCs), which define the shape of the adult hermaphrodite gonad. 12 Interestingly, expression of CED-5(1-1715) in CED-5-deficient worms was able to rescue DTC migration as efficiently as the wild-type CED-5 (Table 1b). These data suggested that the direct interaction of CED-2 and CED-5 is not required for efficient engulfment or DTC migration in C. elegans.…”
Section: Resultsmentioning
confidence: 94%
“…The small GTPase RhoG has recently been suggested to mediate ELMO : Dock180 complex recruitment to the membrane, in turn potentially regulating Rac activation during engulfment. 12,13 We next asked whether RhoG might serve as a link between the CrkII and the Dock180 : ELMO submodules. When we coexpressed a dominant-negative form of RhoG (RhoG T17N ) with CrkII, it was able to partially inhibit CrkII-mediated phagocytosis ( Figure 6, compare bars 8-2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four different signaling pathways act upstream of this heterotrimeric CED‐5/Dock180, CED‐12/Elmo, CED‐2/Crk‐II GEF complex to activate it in the cell (Fig. 4B): (B.1) One goes through the GEF UNC‐73/Trio, which activates the small GTPase MIG‐2 /RhoG and hence regulates the CED‐5/Dock180‐CED‐12/Elmo GEF complex 65 and recruits it to the membrane.(B.2) Wnt pathway components, between the frizzled receptor and APR1/APC, act genetically upstream of CED‐10/Rac during cell corpse engulfment. In C. elegans , stimulation of the Wnt pathway leads to activation of the glycogen synthase kinase GSK‐3, which acts in a complex with APR‐1/APC.…”
Section: Ced‐10/rac Is At the Core Of The Phagocytosis Of Apoptotic Cmentioning
confidence: 99%
“…(B.1) One goes through the GEF UNC‐73/Trio, which activates the small GTPase MIG‐2 /RhoG and hence regulates the CED‐5/Dock180‐CED‐12/Elmo GEF complex 65 and recruits it to the membrane.…”
Section: Ced‐10/rac Is At the Core Of The Phagocytosis Of Apoptotic Cmentioning
confidence: 99%